Review: Rehabilitation of Schizophernia: At the End or in the Beginning? - Farbod Fadaei (University of Social Welfare and Rehabilitation Sciences, 2006)
The majority of the long stay psychiatric patients who are in need of rehabilitation, consist of people suffering from schizophrenia. Most of them have entered old age with their above mentioned illness and besides the consequences of schizophrenia, are facing the deprivation and suffering due to their old ages. In contrast to the previous decades that there have not been an effective treatment for schizophrenia, today with the immediate diagnosis and treatment of schizophrenia with effective medications, one can prevent chronicity and resistance to their treatment. By these means one can improve the prognosis and the quality of life of patients and their caregivers. Since ten years ago the artificial discrimination of schizophrenic patients to chronic and non-chronic has lost its validity. It is recommended in spite of presenting the special and isolated hospitals for the mentally ill, also psychiatric wards in the general hospitals may be included. By all these measures the schizophrenics can have a better treatment and rehabilitation and can be saved from the social and psychological consequences of staying in the isolated mental hospitals.